Hiding from humanity : disgust, shame, and the law - Nussbaum, Martha C. (Martha Craven), 1947- (Princeton University Press, 2004)
Should laws about sex and pornography be based on social conventions about what is disgusting? Should felons be required to display bumper stickers or wear T-shirts that announce their crimes? This powerful and elegantly written book, by one of America's most influential philosophers, presents a critique of the role that shame and disgust play in our individual and social lives and, in particular, in the law. Martha Nussbaum argues that we should be wary of these emotions because they are associated in troubling ways with a desire to hide from our humanity, embodying an unrealistic and sometime.
Keywords: Law -- Psychological aspects.; Droit -- Aspect psychologique.; LAW -- Jurisprudence.; LAW -- General Practice.; LAW -- Reference.; LAW -- Essays.; LAW -- Paralegals & Paralegalism.; LAW -- Practical Guides.; LAW -- Ethics & Professional Responsibility.; Law -- Psychological aspects